Pengaruh Akrual, Leverage, Dan Arus Kas Operasi Terhadap Persistensi Laba Dengan Book Tax Differences Sebagai Variabel Moderasi - Veronika; Herlin Tundjung Setijaningsih (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2022)
This research aims to analyze the effect of accruals, leverage, and operating cash on earnings persistence by using the book tax difference as moderation in manufacturing companies listed on the Indonesia Stock Exchange during 2018-2020. The sample was selected by purposive sampling method as many as 40 companies with a total of 120 data for three years. The data technique uses multiple regression analysis and is processed with Eviews 12.0 and Microsoft Excel 2013. The results of this study indicate that: 1) Accruals, leverage, and operating cash flow have significant effect on earnings persistence; 2) The difference in book tax does not strengthen the effect of accruals, leverage, and operating cash flows on earnings persistence; 3) The difference in book tax does strengthen the effect of operating cash flows on earnings persistence.